The Human Eye as a Visual Symbol for Expressing Feelings of Loss in Contemporary Art: An Analytical Study of a Group of Contemporary Artists (Al-Academy, 2025)
This study addresses the topic of loss as one of the most profound and impactful human experiences, examining how the human eye is used as a visual symbol to express feelings of grief and the stages of accepting loss in contemporary art. The study seeks to provide a deeper understanding of the role of the human eye as a visual symbol and a visual medium that reflects various emotional reactions, by examining some contemporary visual practices. The importance of the research is highlighted by the integration of physiology and artistic symbolism, which opens a new horizon for developing artworks that express complex emotional experiences.          The study relied on a descriptive and analytical approach by reviewing and analyzing selected artworks by contemporary artists. Artists relied on the human eye as a primary symbol of expression and as a visual medium that has not been sufficiently employed artistically. The study also focused on the use of symbolic connotations associated with the eye, in addition to examining the physiological changes that occur in the eye during grief, through a review of relevant scientific and artistic literature. A purposive sample of five artworks by artists who used the eye in various expressive ways was analyzed.        The results showed that the human eye is a powerful visual tool for expressing feelings of loss as well as various emotional feelings. The characteristics of the iris and pupil change depending on the emotional state of the artwork, enhancing the impact of the artwork on the recipient. The study also demonstrated the diversity of eye symbolism among the artists under study. The paper recommends further research linking human physiology to contemporary visual practices, particularly encouraging artists to explore the manifestations of the human eye as a symbol for expressing profound human experiences, with a focus on using innovative techniques and materials to enrich visual art.